Rembrandt’s Anatomy Lesson of Dr. Tulp Revisited: Advancements in Teaching Anatomy and Neurobiology in an Integrated Medical Curriculum in the 21st Century. - Tulp, Orien; Frantz Sainvil,; Hailin Wu,; Rolando Branly, (British Journal of Healthcare and Medical Research, 2023)
The recent challenges in anatomy and neurobiology education in medical curricula have imposed a curricular redevelopment in delivery and content, incorporating modules in virtual anatomy and neurobiology, didactic lecture and enhanced cadaveric dissection in a state-of-the-art teaching and learning environment. The combined approach engaged active student participation at each phase of the course, incorporated clinical perspectives, emphasized valuable diagnostic and surgical techniques and procedures, and minimized noxious exposure to formaldehyde by using unembalmed cadavers in a laminar airflow environment. Finally, the objectives of emphasizing the importance of proficiency in anatomy knowledge in clinical medicine were accomplished well within the allocated one semester time frame, in a timely, cost and resource effective manner, and with demonstration of competency to standard during post laboratory examinations.